Mennesket i myreperspektiv: Secret Hotels Vandringsforelæsning om Myrer som antropocæn poetik - Nielsen, Thomas Rosendahl (K&K - Kultur og Klasse, 2020)
How is it possible to establish a ”vantage point from the earth’s surface” (Latour) through participatory performance art? In the ”walking lecture” Vandreforelæsning om myrer (2017) the Danish performance theatre Secret Hotel combined immersive theatre strategies with scientific lectures in a performance that challenged anthropocentric perspectives by inviting the audience to imagine and explore the perspectives of the ant. This essay discusses this work in dialogue with the eco-critical thinking of Timothy Morton and outlines how this work contributes to a poetic of the Anthropocene. The analysis observes how the performance establishes ”weird loops” (Morton) and how these weird loops enable what Morton has called ”ecognosis”: an ecological awareness that transcends the human perspective and lets us become accustomed to the strange other beings with whom we coexist. The analysis identifies three contributions to a poetic of the Anthropocene that aims to challenge anthropocentrism: 1) Giving form to that which can be described, but not easily sensed. 2) Making the spectator’s loop of knowledge (ecognosis) an intrinsic part of the work of art. 3) Establishing coherence in the work of art through the principle of subscendence: the whole is less than the unity of its parts.